Facilities planning and materials handling methods and requirements - Sheth, Vijay S. (Manufacturing engineering and materials processing, 1995)
This work details the techniques necessary to perform accurate analysis of factory flow and layout and to select, install and test advanced manufacturing equipment. It discusses new technologies applicable to all aspects of facilities planning and materials handling and storage, including computerized flow-simulation programs and authomatic storage, retrieval and guided vehicle systems.